Optimization of land use and land protection in dangerous erosion agricultural landscapes - Tymoshevskyi, V.; Litvinenko, T.; Ilchenko, V. (Land Management, Cadastre and Land Monitoring, 2017)
The main aims of the article is the research areas of optimization of land use and land protection of agricultural landscapes. According to this in the article analysis of the degradation processes in agricultural landscapes, development of land management projects as a tool for optimization of land use and protection of agricultural landscapes are discussed. Theoretical and methodological basis of research is dialectical theory of knowledge, the comprehensive, systematic approach to the study of foreign experience and national practice of investigated problems, use of general and special methods of basic laws and regulations of economic theory. Much attention is given to the negative phenomena of agricultural land use, including water erosion and formation the ways of economically efficient, ecologically safety and socially oriented land use. Studied the experience of foreign countries on the mechanism of land use and providing safety use in dangerous erosion agricultural landscapes. Caused by anthropogenic degradation processes in agricultural landscapes mainly due of the intensity of cultivation, use of erosion dangerous lands, breach of crop rotation, decrease area with grasses crop, unsystematic use of natural grasslands. Conscious of the needs to implementation control of erosion, land users don’t do it at once and quickly. Because economic activity while profits more than production costs or costs associated with the implementation of erosion control measures, including contour-reclamation organization of territory. However, in the future this approach could lead to economically efficient, socially and environmentally threatening and dangerous land use. Land has a number of features that distinguish it among other resources. Such as means of production and the subject of labor in agriculture and forestry, base of industries location, environmental and social regulator etc. Therefore, there is a need to preserve and improve the properties of the land for future generations. Providing an integrated approach to planning land use and protection, including protection of soil in the context of sustainable development is one of the basic key of "Agenda XXI", "Strategy for sustainable development of Ukraine - 2020" and "Sustainable development of Ukraine during 2016-2030". In the context of a new climate agreement established by Paris conference where marked action by conservation and increasing absorbent of greenhouse gases, an important role as a ground like controller carbon and nitrogen cycles. High capacity for carbon sequestration are degraded soils in the process of restoring their properties. Potential of soil for absorption and retention of carbon can be increased by soil-reproduction techniques, including erosion control measures. Land management is quite a tool that has evolved to a multi-role that should provide a basis for decision-making in all areas related with land and land use. Therefore, development and implementation of land management projects of land use and protection can be and should be the basis for the implementation of safety land use in dangerous erosion agricultural landscapes. These projects will provide slowing and stopping anthropogenically accelerated erosion processes from one hand, and ensure efficient economic activity from other. Land management projects should include land zoning for allotment of eco-technology groups of arable land, according to which a decision on further land use and development of agricultural landscapes and placing shelterbelts, which should be an essential component of landscapes. Therefore, for safety land use in dangerous erosion agricultural landscapes consider the following: the differential use of agricultural land depending of soil cover and relief; observance of safe slope drainage of runoff; meadow slopes along drainage channels; shelterbelts placement systems for water and wind regulatory. Keywords: land use, agricultural landscapes, land degradation, erosion, land management, protection of soil.